Enhancing Student Participation in University Policy Making to Prevent Campus Violence - Syamsudduha Syamsudduha; Sukirman Sukirman (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This qualitative study explores how student participation in university governance relates to campus violence in an Indonesian public university. The main goal is to understand how the lack of student involvement in decision-making can lead to protest and conflict. Data were collected exclusively through in-depth interviews with students. To strengthen the credibility and validity of the findings, the research employed data triangulation through two rounds of interviews. The second round was conducted to clarify, confirm, and further explore statements that were unclear or incomplete in the first round. In addition, selected interview excerpts and preliminary interpretations were shared with all participants to ensure that the analysis accurately reflected their perspectives. The findings show that when students are excluded from important decisions, such as when their petitions are ignored, policies are made without consultation, or security officers respond harshly, their trust in university leaders declines. As a result, peaceful demonstrations often turn into confrontations. These events are not sudden or irrational but develop from repeated neglect and frustration. On the other hand, examples of genuine collaboration, such as student–staff committees and joint policy discussions, help reduce tension and create a more positive campus atmosphere. The study also highlights a major challenge in Indonesian higher education: although democratic systems exist, many universities still employ top-down practices that limit students' real influence. The research concludes that student violence is a response to governance problems rather than a natural tendency toward aggression. By combining ideas from participatory governance, conflict resolution, and student activism, this study shows that involving students in real decision-making can build trust and prevent conflict. Overall, the findings suggest that a true partnership between students and administrators is essential for improving university governance and strengthening democracy in post-authoritarian societies.